(untitled) - Field, Barry C. (Boston, 2006)
This work includes twenty-one chapters covering Cost and Benefits of Environmental Policy, Environmental Analysis, Policy Analysis, US Policy (Air Pollution, Toxic Wastes, State and Local Issues), and International Environmental Issues.
Keywords: Environmental economics,Economic development; Environmental aspects